Philosophy and dietetics in the Hippocratic On regimen : a delicate balance of health - Bartoš, Hynek. (Studies in Ancient Medicine, 2015)
This book offers the first extended study published in English on the Hippocratic treatise On Regimen , one of the most important pre-Platonic documents of the discussion of human nature and other topics at the intersection of ancient medicine and philosophy. It is not only a unique example of classical Greek dietetic literature, including the most elaborated account of the micro-macrocosm and phusis - technē analogies, but it also provides the most explicit discussion of the soul-body opposition preceding Plato. Moreover, Bartoš argues, it is a rare example of an extant medical text which systematically draws on philosophical authorities, such as Heraclitus, Empedocles and Anaxagoras, and which had a decisive influence on both physicians, such as Galen, and philosophers, most notably Plato and Aristotle.